Complications associated with hospitalization after spinal cord injury - Wilczyński, Michał; Szmelcer, Beniamin Piotr; Krakowska, Natalia; Fortuna, Aleksandra; Wszelaki, Patrycja; Florczak, Aleksander; Zaborna, Daria; Ciepłuch, Justyna; Gajos, Małgorzata; Skierkowska, Natalia; et al. (Journal of Education, Health and Sport, 2019)
Abstract: Background: Spinal cord injuries are a traumatic phenomenon not only for the physical sphere, but equally affect the human psyche. The patient ceases to be independent in his actions, he must face a completely new situation for himself and the environment. Particularly difficult is the first period after injury, associated with hospitalization. That is why it is so important to prevent the most common complications of spinal injuries during this period. Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: Spinal Cord, Injury, Trauma, Complications Results: The most common complications associated with the hospital stay of patients with spinal cord injury include: complications in the respiratory system (including pneumonia, atelectasis and respiratory failure), decubitus ulcers, periarticular neurogenic ossification, autonomic dysreflexia, spasticity or disorders in the functioning of the urinary tract. Decubitus ulcers due to their nature are a huge problem for hospitalized patients, in epidemiological studies it was estimated to occur at nearly 20 per cent. Spasticity is one of the most serious complications hindering the effective rehabilitation process of post-traumatic persons. In the case of disorders associated with the urinary system, it is important to classify dysfunctions based on the neurogenic evaluation of the sphincter muscles and detrusor. Conclusions: Due to the increasing number of spinal cord and spinal cord injuries and the serious nature of their complications, this topic should continue to be an area of very intensive scientific research, both theoretical and clinical. The given issues should be familiar not only to the medical community but also to the family and the patient’s environment.